2013
DOI: 10.4103/0970-9290.114913
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strain generated in bone by "platform-switched" and "non-platform-switched" implants with straight and angulated abutments under vertical and angulated load: A finite element analysis study

Abstract: In spite of the obvious advantages, the practice of immediate loading is limited due to apprehension associated with compromised bone response and a higher rate of bone loss around an immediately loaded implant. The mechanical basis for the concept of "platform switching" in immediately loaded situation is analyzed in this context. The results of this limited investigation indicated that the ideal values of microstrain (50-3000 microstrain) can be exhibited by platform switching of dental implants (with an abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Regardless of the methodology and implants used, the results of our study corroborate the results reported by other studies [28][29][30][31], which demonstrated that the area of the cortical bone crest is always more exposed to harmful forces, especially when non-axial loads are applied. The concern with the dissipation of loads in the region of the marginal ridge is a constant in several studies found in the literature since stress concentrations above the flow limit can cause microfractures in the cortical bone area and induce bone resorption.…”
Section: Plos Onesupporting
confidence: 91%
“…Regardless of the methodology and implants used, the results of our study corroborate the results reported by other studies [28][29][30][31], which demonstrated that the area of the cortical bone crest is always more exposed to harmful forces, especially when non-axial loads are applied. The concern with the dissipation of loads in the region of the marginal ridge is a constant in several studies found in the literature since stress concentrations above the flow limit can cause microfractures in the cortical bone area and induce bone resorption.…”
Section: Plos Onesupporting
confidence: 91%